Coeliac disease in identical twin infants. Issue 672 (October 1981) - Lord, C.; MacGregor, Gerald A.
Abstract : A pair of monozygous twins had coeliac disease in infancy, and all of their family carried the HLA-B8 antigen. Both genetic and environmental factors were involved in the aetiology.